GIS-Based Approach For Mapping Of Oil-Based Pollutant Concentration Along The Sg. Galing, Kuantan - Baxtier Brandon, Juheng (2023)
The increasing rate of industrialization and urbanization around Sg Galing can pollute the river and affect the natural source of fresh water for human activities. Other than that, lack of enforcing water security causes the river to be more polluted and illegal activities are uncontrolled. Aquatic life and the environment may be harmed by these causes. Conventional method to monitor the water quality is not effectively as the cost and time constraint would be its challenges. Thus, GIS technology is an alternative to solve the issue and offers repetitive monitoring at helicopter view which enable coverage of the whole Sg. Galing. Water is a basic need of human life. Clean water is essential for various routine activities and environmental processes. Water pollutants include contamination because of domestic wastes, pesticide and chemical substance, food processing waste, pollutants from livestock operations and many other sources. Using a spatial technological tool, namely GIS approach, this study focuses on mapping water pollutants in Sg. Galing, Kuantan. To determine which areas are severely polluted, high, medium, and low pollutant concentrations would be spatially interpolated along the river. A GIS processing system would be used to determine which sources of pollution contributed the most to the map's pattern. One of the most common causes of river water pollution is oil pollution. Manufacturing industries, man-made activities, and accidents in which oil is dumped or spilled into a river, polluting the water, can all be blamed for this. These are potentially hazardous to humans, aquatic life, and the environment. The map and analysis generated from this study could help decision makers and local authorities to provide immediate mitigation action to prevent further pollution into the water system of Sg. Galing, aligned with SDG 11: Sustainable cities and communities; and SDG 14: Life below water.